Problems Of Developing Creative Thinking In Mathematics Learning - Pramida, Intan; Rosiatuningsih; Kusno (Universitas Islam Negeri Raden Intan Lampung, 2026)
The limited development of creative thinking in mathematics education reflects a fundamental gap between conventional instructional practices and the cognitive demands of contemporary learning. Many learning environments still emphasize procedural knowledge, restricting students’ opportunities to generate, explore, and refine mathematical ideas. This study aims to examine how creative thinking can be fostered through the integration of problem posing and Project-Based Learning in mathematics education. A systematic literature review was conducted by analyzing selected peer-reviewed studies indexed in Scopus, focusing on instructional approaches that support creative thinking development. The analysis was guided by four key dimensions of creative thinking: fluency, flexibility, originality, and elaboration. The findings reveal that problem posing functions as a generative mechanism that promotes idea production and originality, while Project-Based Learning operates as a contextual mechanism that supports idea refinement and elaboration. The interaction between these approaches facilitates the development of flexibility as a connecting dimension between idea generation and contextual application. Based on these findings, this study proposes an integrated conceptual model that explains how generative and contextual processes interact to support the multidimensional development of creative thinking. This model offers a more dynamic and process-oriented perspective that moves beyond the use of isolated instructional strategies. The study contributes to advancing theoretical understanding while also providing practical insights for designing mathematics learning environments that foster meaningful and sustainable creative thinking.